Backstepping based power control of a three-phase Single-stage Grid-connected PV system - Mohammed El malah; Abdellfattah Ba-razzouk; M’hammed Guisser; Elhassane Abdelmounim; Mhamed Madark (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In order to reduce costs while maintaining superior performance, this paper presents a new control methodology of a three-phase grid connected photovoltaic system without using the intermediary DC/DC converter. Based on the synchronized nonlinear model of the whole photovoltaic system, two controllers have been proposed for the three-phase inverter in order to ensure the operation of the PV system at the maximum power point with unity power factor and minimum grid disturbance. Grid synchronization has been ensured by a three-phase 2nd order PLL (Phase-Locked Loop). The stability of each controller is demonstrated by means of Lyapunov analysis and evaluated under changing atmospheric conditions using the Matlab/Simulink environment, the simulation results clearly demonstrate the performance provided by each controller.